Analysis of Potential Sector Investment Needs in Increasing Growth Economy in East Java - Nugrahani, Ajeng Putri; Hendrati, Ignatia Martha (MediaTrend, 2024)
Investment is the main means to encourage economic growth. Investment realization in 2019 and 2020 has a positive trend. However, despite the positive trend, investments made in 2019 and 2020 are unlikely to have a positive impact on economic growth in East Java Province. In order for investment to be more efficient in its allocation, it is important for a region to know the need for investment in economic sectors, especially in potential economic sectors.  To analyze the potential sectors in East Java Province, use the Klassen Typology analysis technique. Meanwhile, to determine the growth target and the amount of investment needs of the potential sector using semi-average analysis techniques, and the Incremental Capital Output Ratio (ICOR). The results of this study concluded that there are four potential sectors in East Java Province, namely (1) mining and quarrying sector, (2) information and communication sector, (3) real estate sector, and (4) education service sector. The investment needed by potential sectors of East Java Province is (1) Mining and Quarrying of IDR 27,650.79 billion, (2) Information and Communication of IDR 29,427.33 billion, (3) Real Estate of IDR 5,834.45 billion, and (4) Education Services of IDR 8,269.42 billion.